1992
DOI: 10.1164/ajrccm/146.2.419
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Registry of Patients with Acute Respiratory Distress Syndrome: Physiology and Outcome

Abstract: In a multicenter registry conducted over 2 yr of patients with acute respiratory distress syndrome (ARDS), we enrolled 153 patients and collected data daily for 7 consecutive days and weekly thereafter until death or hospital discharge. The purposes of the registry were (1) to determine whether a more liberal definition of ARDS (PaO2/FIO2 < or = 250; bilateral pulmonary infiltrates within 7 days) than those commonly used would result in enrollment of patients earlier in their clinical course, and (2) to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
2
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(148 citation statements)
references
References 4 publications
10
127
2
9
Order By: Relevance
“…Th ese fi ndings are concordant with several studies that have shown that the PF ratio measured at the onset of ARDS is not an independent predictor of mortality. [20][21][22][23][24][25] One possible explanation for the lack of the power of the PF ratio to discriminate adverse outcome in ARDS is that the PF ratio is highly variable depending on the ventilator strategy chosen. In one study, standardization of ventilator settings greatly improved risk stratifi cation of ARDS by PF ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Th ese fi ndings are concordant with several studies that have shown that the PF ratio measured at the onset of ARDS is not an independent predictor of mortality. [20][21][22][23][24][25] One possible explanation for the lack of the power of the PF ratio to discriminate adverse outcome in ARDS is that the PF ratio is highly variable depending on the ventilator strategy chosen. In one study, standardization of ventilator settings greatly improved risk stratifi cation of ARDS by PF ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with adult respiratory distress syndrome older age is clearly associated with higher mortality rates. 87,88 Similar data specific to mechanical ventilation made necessary by postoperative pulmonary complications are not available. Ely et al 89 prospectively studied whether age represents an independent effect on the outcomes of patients requiring mechanical ventilation after admission to an intensive care unit.…”
Section: Non-invasive Ventilationmentioning
confidence: 99%
“…The differential diagnosis is challenging in cases requiring distinction between cardiogenic pulmonary edema (CPE) and ARDS/acute lung injury (ALI). [1][2][3][4][5] The most widely used clinical definition of ARDS/ALI is based on the acute onset of hypoxemia, chest radiography, risk factors, and a pulmonary capillary wedge pressure (PCWP) < 18 mm Hg, or absence of clinical evidence of elevated left atrial filling pressures. 3 However, clinical estimation of PCWP is notoriously inaccurate, 6 and its measurement requires the performance of right-heart catheterization (RHC) using a Swan-Ganz catheter, which is invasive and costly, 7 and has been associated with neutral 8-10 or potentially adverse clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%